Essential oils of Zingiber officinale: Chemical composition, in vivo alleviation effects on TPA induced ear swelling in mice and in vitro bioactivities - Zhang, Silu; Zhang, Lijun; Yu, Mengjie; Luo, Donghui; Chen, Shuai; Liu, Weifeng; Zhang, Yehui; Zhang, Lanyue; Zhao, Tiantian (Frontiers in Nutrition, 2022)
Zingiber Officinale (ZO) is a traditional food condiment. The essential oils of Zingiber Officinale (ZOEOs) are known to have multiple bioactivities. In this study, gas chromatography mass spectrometer (GC-MS) analytical method was used to identify active ingredient present in ZOEOs. A total of 41 compounds were identified in ZOEOs. Major components in ZOEOs were zingiberene (19.71 %), (+)-β-cedrene (12.85 %), farnesene (12.17 %), α-curcumene (10.18 %) and β-elemene (3.54 %). Experimental results of 12-O-tetradecanoylphorbol-13 acetate (TPA) induced ear swelling validation mice model showed that ZOEOs treatment has better anti-inflammatory effect compared with ibuprofen (positive control) at high concentrations. Histological and immunohistochemical analysis showed that ZOEOs significantly decreased COX-2, IL-6 and NF-κB expression in a dose dependent manner. The mRNA levels of COX-2 and NF-κB were also down regulated by the application of ZOEOs. Antibacterial experimental results showed that EOZOs had anti-bacterial effects on Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus. DPPH radical scavenging, A549 cell line and LNCaP cell line inhibition results indicated that ZOEOs exhibited potential antioxidant and anti-tumor properties. The findings of these study provide scientific basis on therapeutic use of ZO in food, cosmetic and pharmaceutical industries.